Votive inscriptions in Linear A - Tomas, Helena (Array, 2002)
Paper discusses votive inscriptions in the Bronze Age Cretan Linear A script still undeciphered. Votive inscriptions on libation tablets, votive cups, a ladle, a figurine, axes, silver pins and a golden ring, are continious texts and should offer some ideas on the sintax of the language as well as of the ritual cotext in which they were used.